A Pharmacogenetically Guided Acenocoumarol Dosing Algorithm for Chilean Patients: A Discovery Cohort Study - Roco, Angela; Nieto, Elena; Suárez, Marcelo; Rojo, Mario; Bertoglia, Maria Paz; Verón, Gabriel; Tamayo, Francisca; Arredondo, Annabella; Cruz, Daniela; Muñoz, Jessica; Bravo, Gabriela; Salas, Patricio; et al. (Frontiers in Pharmacology, 2020)
Background Vitamin K antagonists (VKA) are used as prophylaxis for thromboembolic events in patients with cardiovascular diseases. The most common VKA are warfarin and acenocoumarol. These drugs have a narrow therapeutic margin and high inter-individual response variability due to clinical and pharmacogenetic variables. Objective The authors aim to develop an algorithm comprised of clinical and genetic factors to explain the variability in the therapeutic dose of acenocoumarol among Chilean patients Methodology DNA was obtained from 304 patients as a discovery cohort with an international normalized ratio (INR) range of 2.0–3.0. The non-genetic (demographic and clinical) variables were also recorded. Genotype analyses were performed using real-time PCR for VKORC1 (rs9923231), VKORC1 (rs7294), GGCx (rs11676382), CYP4F2 (rs2108622), ABCB1 (rs1045642), CYP2C9*2 (rs1799853), ApoE (rs429358), and CYP2C9*3 (rs1057910). Results The clinical variables that significantly influenced the weekly therapeutic dose of VKA were age, sex, body mass index (BMI), and initial INR, collectively accounting for 19% of the variability, and the genetic variables with a significant impact were VKORC1 (rs9923231), CYP2C9*2 (rs1799853), and CYP2C9*3 (rs1057910), explaining for another 37% of the variability. Conclusion We developed an algorithm that explains 49.99% of the variability in therapeutic VKA dosage in the Chilean population studied. Factors that significantly affected the dosage included VKORC1, CYP2C9*2, and CYP2C9*3 polymorphisms, as well as age, sex, BMI, and initial INR.